#SoMe4Surgery: from inception to impact. Issue 2 (3rd February 2020) - Grossman, Rebecca C; Mackenzie, Douglas Graham; Keller, Deborah S; Dames, Nicola; Grewal, Perbinder; Maldonado, Andrés A; Ioannidis, Argyrios; AlHasan, Ameera; Søreide, Kjetil; Teoh, Jeremy Yuen-Chun; Wexner, Steven D; Mayol, Julio
Abstract : Objectives and setting: The aim of this study was to create a hashtag #SoMe4Surgery on the social network application Twitter, and to examine the natural history of the resulting online community. Design and outcome measures: A prospective, four-stage framework was proposed and used: (1) inception phase (connection): users were actively invited to participate; (2) dissemination phase (contagion): several tweetchats were designed, scheduled and run; (3) adherence phase (feedback): Twitonomy and NodeXL summaries were regularly posted on Twitter; and (4) impact phase (outcomes): abstracts and manuscripts, and related projects on Twitter. Tweets, influencers and interactions were analysed, and a brief survey was shared with participants to assess demographics and motivations of social media use. Participants: Users engaging with the #SoMe4Surgery hashtag. Results: Users of the hashtag came from a wide variety of specialties and geographical locations, as well as varying in age and stage of training. The inception of #SoMe4Surgery was followed by an increase in the follower count and impressions of users. A total of 675 tweeters posted 11 855 tweets with 30 122 retweets between 28 July and 27 December inclusive. There were new contributors and activity throughout the period. There were many more retweeters than accounts posting original content. Over a 10-day period ending on 31 December 2018, the number of followers of the 10 most influential accounts was higher than the number of followers of the 10 most engaging accounts (p=0.002). The mean (SD) number of tweetchat participants was 121 (64), who posted 719 (365) tweets and had a potential reach of 3 825 155 (1 887 205) accounts. Spin-off projects included surveys from low and medium-income countries, subspecialised hashtags, presentations and one publication. Conclusions: The creation of a cohesive online surgical community may allow a flattened hierarchy, with increased engagement between surgeons, other healthcare professionals, researchers and patients.